(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The hypothesis of a rise of "neurolaw" shall not be accepted as an obvious and universal truth without taking civil cases and civil law into consideration. This article is intended as a contribution to the discussion, analyzing rulings on cases which mentioned MRIs and brain scans as evidence to challenge the validity of civil legal instruments, based on a claim of mental incompetence (also called "insanité") in France and in the USA The aim of the study is to test an hypothetical "fascination effect" on judges and to evaluate the true impact in civil jurisprudence of this type of evidence.